2019
DOI: 10.1088/1757-899x/698/5/055004
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative state improvement of public and courtyard areas in terms of Rostov-on-Don

Abstract: Today the most important task in the development of modern Russian cities is the environment formation and maintenance that is favorable and comfortable for the population. The authors of the article revealed the main state problems of public and courtyard territories in Russian cities. Programs analysis of the urban areas improvement for the period from 2018 to 2022, aimed at the development of the urban environment provides an example of its successful implementation as applied to the city of Rostov-on-Don.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Greenery is positively associated with leisure activities, which was shown by the regression analysis. Within an urban environment, greenery provides favorable living conditions [ 102 ], and seniors prefer to stay in their community and walk around green spaces during the time they exercise outside [ 103 ]. As such, it is suggested that local governments and councils focus on maintaining and increasing greenery-filled public areas that are convenient to walk in and are within easy walking distance of each residential building [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greenery is positively associated with leisure activities, which was shown by the regression analysis. Within an urban environment, greenery provides favorable living conditions [ 102 ], and seniors prefer to stay in their community and walk around green spaces during the time they exercise outside [ 103 ]. As such, it is suggested that local governments and councils focus on maintaining and increasing greenery-filled public areas that are convenient to walk in and are within easy walking distance of each residential building [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a self-cleaning effect is created on the tile surface, the mechanism of which is that water flows under the dirt on the tile surface, washing it off, and in addition, when quanta are absorbed, a reaction occurs that splits the dirt on the tile. When absorbing quanta (ultraviolet radiation), it exhibits disinfecting properties [12].…”
Section: K2so4·al2(so4)3 → K2so4 + Al2o3 + 3so2mentioning
confidence: 99%
“…Modern society is developed according to the principles of sustainable development, the main ones of which are: improving human living conditions in terms of environmental impact within the economic capacity of the biosphere; satisfaction of needs in the present without prejudice to future generations [1,2]. The leading form of territorial and socioecological-economic organization of modern society is the city as a system.…”
Section: Introductionmentioning
confidence: 99%